LncRNA HCG11 regulates proliferation and apoptosis of vascular smooth muscle cell through targeting miR-144-3p/FOXF1 axis in atherosclerosis - Yi Liu (Biological Research, 2020)
Abstract Background Atherosclerosis (AS) is the main pathological basis of coronary heart disease, cerebral infarction and peripheral vascular disease, which seriously endanger people’s life and health. In recent years, long non-coding RNA (lncRNA) has been found to be involved in gene expression regulation, but the research on AS is still in the initial stage. In this study, we mainly studied the role of HCG11 in patients with AS. Quantitative Real-time Polymerase Chain Reaction (QRT-PCR) was used to detect the expression of HCG11 and miR-144 in the serum of AS patients and healthy volunteers. Oxidation Low Lipoprotein (Ox-LDL), interleukin-6 (IL-6) and tumor necrosis factor α (TNF α) radiation were used to establish human vascular smooth muscle cells (VSMCs) in vitro model. Cell proliferation was determined by Cell Counting Kit-8 (CCK-8) assay. The apoptosis rate was determined by flow cytometry (FACS) and terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling assay (TUNEL) staining. The expression levels of Forkhead box protein F1 (FOXF1), B cell lymphoma-2 (Bcl-2) and BCL2-Associated X (Bax) were detected by qRT-PCR. Luciferase gene reporter and RNA pull down experiments confirmed the relationship between HCG11 and miR-144, miR-144 and FOXF1. Results This study showed that HCG11 was significantly upregulated in patients with AS, while miR-144 was down-regulated in patients with AS. Ox-LDL and IL-6 in VSMCs induced up-regulation of HCG11 and down-regulation of miR-144. Overexpression of HCG11 promoted the proliferation and inhibited apoptosis of VSMCs. Luciferase gene reporter gene assay showed that HCG11 could bind to miR-144, and miR-144 could bind to FOXF1. Overexpression of miR-144 reversed the effect of HCG11 on VSMCs. Conclusions LncRNA HCG11 regulates proliferation and apoptosis of vascular smooth muscle cell through targeting miR-144-3p/FOXF1 axis.